Problems related to incomplete securities and alternative solutions through the use of ICT and new technologies - Cortijo Gonzales, Jessica Katherine (2023)
The objective of this article is to determine how to provide legal certainty to the principal in the execution of an incomplete security that has been completed in a manner contrary to the agreements made. The methodology is basic, using a qualitative approach of an analytical nature to provide a solution to a real phenomenon. It has also been developed through a systematic review study. The main theoretical bases are the description of the socio-legal problems related to incomplete securities, as well as the proposal of application assumptions in order to be able to resolve existing conflicts by making use of the so-called ICT (Information and Communication Technologies) and new technologies. It is concluded that an adequate and viable legal regulation of the act of accepting and issuing incomplete securities is necessary in order to ensure their full legal effectiveness and an adequate defence of the   principal, in which the State plays a fundamental role.